Genetically modified (VIP) cotton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Lucia Muza of the Quton company on the potential offered by Syngenta?s VIP cotton to small-scale farmers in Zimbabwe.